Wykorzystanie filmu edukacyjnego Niebieskoocy na zajęciach ze studentami - Jakubowska-Baranek, Justyna (Kultura-Społeczeństwo-Edukacja, 2016)
In the article I discuss the subject matter of the educational film Blue Eyed in terms of using its wide cognitive and educational advantages in academic class with students. The subject matter is discussed in the context of dominant media culture. I stress the meaning of multimedia in creating social reality image and present multiplicity of an educational film's features.